Volume 6: Structures and Dynamics, Parts a and B 2011
DOI: 10.1115/gt2011-45880
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Convective Inertia Effects in Plain Journal Bearings With Eccentricity, Velocity and Acceleration

Abstract: Fluid film bearings are commonly analyzed with the conventional Reynolds equation, without any temporal inertia effects, developed for oil or other high viscosity lubricants. In applications with rapidly time varying external loads, e.g. ships on wavy oceans, temporal inertia effect should be taken into account. As rotating speeds increase in industrial machines and the reduced Reynolds number increases above the turbulent threshold, a form of linearized turbulence model is often used to increase the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…They suggested that at small eccentricity ratios, where the effect of temporal inertia is dominant, an added mass is produced, which corresponds to the radial direct inertia coefficient, however, at large eccentricity ratios, where the effect of convective inertia is superior, this effect is completely reversed. Dousti et al [18] developed an extended short bearing Reynolds equation that is applicable to both laminar and turbulent flow regimes. Alternatively, according to the perturbation technique [10,19,20], a small first-order perturbation by means of the expressions for the fluid film velocity components and the lubricant pressure distribution that are typically expanded in power series of the squeeze film Reynolds number is applied to the flow equations.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that at small eccentricity ratios, where the effect of temporal inertia is dominant, an added mass is produced, which corresponds to the radial direct inertia coefficient, however, at large eccentricity ratios, where the effect of convective inertia is superior, this effect is completely reversed. Dousti et al [18] developed an extended short bearing Reynolds equation that is applicable to both laminar and turbulent flow regimes. Alternatively, according to the perturbation technique [10,19,20], a small first-order perturbation by means of the expressions for the fluid film velocity components and the lubricant pressure distribution that are typically expanded in power series of the squeeze film Reynolds number is applied to the flow equations.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of momentum equations based on the short bearing assumption leads to the neglect of all shear and inertia terms in the circumferential direction, which limits the applicability of the obtained extended Reynolds equation to short bearings in this work. The current paper can be considered a continuation of the earlier work by Dousti et al [38] including all relevant inertia terms for finite length bearings.…”
Section: Introductionmentioning
confidence: 95%
“…This motion entails centrifugal acceleration, which necessitates the inclusion of temporal inertia in the extended Reynolds equation. Dousti et al [38] developed a new extended Reynolds equation for short fixed geometry bearings. They adopted Constantinescu's model to include turbulence and convective inertia terms [27,30], and accounted for temporal inertia as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive debate on the properties of inertial effects of fluid on lubricant bearing steadiness observing that inertial special contribution are noteworthy in calculation of the rotor steadiness quantities is done by Kakoty and Majumadar [34]. As presented in recent researches [35][36][37][38][39][40][41][42] the inspiration of the ultrafine extracts on hydrodynamic oils lubrication and vibration and friction of the fluid flow film bearings greased with the with ultrafine spices.…”
Section: Introductionmentioning
confidence: 99%